The Effect Method of Playing Finger Painting on Creativity Ability And Ability To Espress Languages In Children Age 5-6 Years - Wulansari, Dewi; Masitoh, Siti; Bachri, Bachtiar S. (Universitas Malikussaleh, 2020)
This study tries to understand the method of playing finger painting on the ability of creativity and express language of children aged 5-6 years. This research was conducted with a quasi-experimental quantitative method